Computational collective intelligence. technologies and applications third International Conference, ICCCI 2011, Gdynia, Poland, September 21-23, 2011, proceedings, Part I - Jedrzejowicz, Piotr; Nguyen, Ngoc Thanh; Hoang, Kiem (Lecture notes in computer science, 2011)
The two-volume set LNAI 6922 and LNAI 6923 constitutes the refereed proceedings of the Third International Conference on Computational Collective Intelligence, ICCCI 2011, held in Gdynia, Poland, in September 2011. The 112 papers in this two volume set presented together with 3 keynote speeches were carefully reviewed and selected from 300 submissions. The papers are organized in topical sections on knowledge management, machine learning and applications, autonomous and collective decision-making, collective computations and optimization, Web services and semantic Web, social networks and computational swarm intelligence and applications.